ANALISIS TINGKAT KESEJAHTERAAN KELUARGA PEMBUDIDAYA IKAN DAN NONPEMBUDIDAYA IKAN DI KABUPATEN BOGOR - Hartoyo Hartoyo; Noorma Bunga Aniri (Jurnal Ilmu Keluarga dan Konsumen, 2010)
Fish farmer families has non-permanent income to fulfill their daily needs. It caused dependence of fish cultivation productivity to capital and quality of environment. This study aimed to analyze welfare level and strategy to improve the family welfare of fish farmer families and to compare with non-fish farmer families. The study used cross sectional design and involved 70 families that consist of 40 fish farmer families and 30 non-fish farmer families as samples. Samples chosen by simple random sampling. The study conducted at Ciseeng Subdistrict, Bogor District from January 2008 until April 2008. The data was analyzed by t-test, chi-square, pearson correlation, sensitivity, specifity, and logistic regression. The welfare level of families that analyzed in this study, using indicators BPS, BKKBN, sociometric, and compound of three indicators. The result showed that only families asset that was significant different between fish farmer families and non-fish farmer families. Sensitivity and specifity analysis by BPS indicator as benchmark showed that sociometric indicator had higher sensitivity and specifity than BKKBN indicator, that was 66,7 and 96,7. Correlation analysis showed that there was significant correlation between BPS and sociometric indicator. Family size and family’s income effected significantly to welfare level of families.